2012
DOI: 10.1177/0044118x12438904
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of the Male Adolescent Identity Crisis

Abstract: Erikson (1950) contends that the physical changes associated with puberty serve as a catalyst for adolescents to question childhood identifications and to consolidate these with current self-conceptions, personal ideologies, interpersonal values, and future aspirations. Erikson describes the adolescent identity crisis as the developmental period when identity development becomes salient. For males, pubertal changes have implications for sexual identity development and self-perceptions of masculinity, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Older adolescent females might be under stress from factors like expectations regarding traditional gender roles and the need for approval from members of the opposite sex. On the other hand, younger adolescent boys might be dealing with the challenges of pubertal changes, the development of their sexual identity, and how they see themselves as men (Jones et al, 2012). Reiss's (2013) systematic review of studies concerning socioeconomic inequalities and mental health problems in children and adolescents found that adolescents from low-income homes were two to three times more likely to have mental health disorders than those from high-income families, and low family socioeconomic status was strongly associated with a higher incidence of mental health challenges in adolescents regardless of gender.…”
Section: Gender Variations In the Correlates Of Depression And Anxietymentioning
confidence: 99%
“…Older adolescent females might be under stress from factors like expectations regarding traditional gender roles and the need for approval from members of the opposite sex. On the other hand, younger adolescent boys might be dealing with the challenges of pubertal changes, the development of their sexual identity, and how they see themselves as men (Jones et al, 2012). Reiss's (2013) systematic review of studies concerning socioeconomic inequalities and mental health problems in children and adolescents found that adolescents from low-income homes were two to three times more likely to have mental health disorders than those from high-income families, and low family socioeconomic status was strongly associated with a higher incidence of mental health challenges in adolescents regardless of gender.…”
Section: Gender Variations In the Correlates Of Depression And Anxietymentioning
confidence: 99%